Knowledge and Income Determining Treatment Options For Cancer Patients - Raden Nabilah Putri Fauziyyah; Oktavia Nur Azizah Jain; Laili Rahayuwati; Lilis Mamuroh; Kusman Ibrahim (Jurnal Berita Ilmu Keperawatan, 2022)
Breast cancer is still the most common case in many countries. Breast cancer can threat a person's quality of life, especially for someone who has difficulty choosing treatment due to lack of understanding of treatment options. In choosing a treatment influenced by knowledge and income which are internal factors that must be present in determining treatment options, because itwill determine the right choice of treatment. This study aims to discover the choice of treatment in breast cancer patients based on knowledge and income.The research design used quantitative descriptive. This study used secondary data from a Leading Tertiary Study grant in 2015. Sampling in this study were 200 breast cancer patients undergoing chemotherapy. Data processing used univariate and crosstabs techniques with the correlation test using Chi-Square.In this study, there was a relationship between knowledge and choice of treatment, but there was no relationship between income and choice of treatment. In conclusion, that the choice of breast cancer treatment is influenced by the respondent's understanding of the disease. It is hoped that this research can be a source of information that can be used by health workers in providing nursing care.